Improved objectivity of grading of TA, 1 transitional cell carcinomas of the urinary bladder by quantitative nuclear and proliferation related features. Issue 11 (1st November 2001) - Bol, M G W; Baak, J P A; de Bruin, P C; Rep, S; Marx, W; Bos, S; Kisman, O
Abstract : Aim —To analyse whether the mean nuclear area of the 10 largest nuclei (MNA-10), the mitotic activity index (MAI), and Ki-67 immunoquantitative features have additional value to discriminate different grades of TA, 1 transitional cell carcinoma (TCC) of the urinary bladder. Materials/Methods —One hundred and fifty of 200 consecutive cases (75%) showing interobserver agreement on duplicate blind grade assessment by independent pathologists were studied. Using random numbers, the 150 cases were divided into sets for learning (n = 75) and testing (n = 75). Single and multivariate analyses were applied to discriminate the different grades in the learning set. The multivariate classifier developed in this way was evaluated in the test set (n = 75). Results —With the MNA-10 alone, using the classification MNA-10 < 80 μm 2 = grade 1, 80 μm 2 < MNA-10 < 130 μm 2 = grade 2, MNA-10 > 130 μm 2 = grade 3, 71% of all 150 cases were correctly classified (69% of grade 1 v grade 2 and 76% of grade 2 v grade 3). With multivariate analysis, the best discriminating features in the learning set (17 grade 1, 30 grade 2, and 28 grade 3) between grades 1 and 2 were MNA-10 and MAI, and between grades 2 and 3 MAI and Ki-67. With these features, 94% of grade 1 v grade 2 and 97% of grade 2 v grade 3 were correctly classified in the learning set (overall, 95% correct, none of the grade 3 cases misclassified). In the test set the classification results were similar. When the three grades were entered at the same time for discrimination, Ki-67 area % and MAI was the best discriminating combination, both in the sets for learning and testing. Overall correct classification results in the sets for learning and testing were slightly lower, but still 94% and 92%. Most importantly, none of the grade 3 cases was misclassified; the classification shifts all occurred between grades 1 and 2. Conclusions —The combination of MNA-10, MAI, and Ki-67 gives much better discrimination between grades 1, 2, and 3 in TA, 1 TCC of the urinary bladder than MNA-10 alone. The similarity of the classification results of the learning set and test set are encouraging and this quantitative pathological grading model should be applied in a prospective study.